2012
DOI: 10.1158/1078-0432.ccr-11-2425
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Combination Study of Olaparib with Cisplatin and Gemcitabine in Adults with Solid Tumors

Abstract: Purpose: To determine the safety and tolerability of olaparib with cisplatin and gemcitabine, establish the maximum tolerated dose (MTD), and evaluate the pharmacodynamic and pharmacokinetic profile of the combination.Experimental Design: We conducted a phase I study of olaparib with cisplatin and gemcitabine in patients with advanced solid tumors. Treatment at dose level 1 (DL1) consisted of olaparib 100 mg orally every 12 hours on days 1 to 4, gemcitabine 500 mg/m 2 on days 3 and 10, and cisplatin 60 mg/m 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 25 publications
6
131
0
Order By: Relevance
“…However, a number of early phase clinical trials have reported severe bone marrow toxicity with such therapeutic combinations [5][6][7][8][9][10] which could in part be attributed to suboptimal dosing schedules. 8 Non-invasive in vivo imaging of PARP-1 using a radiolabeled PARPi and techniques such as Positron Emission Tomography (PET) or Single-Photon Emission Tomography (SPECT) could be used to assess the duration of PARP-1 inhibition in different tissues. This could subsequently guide dosing decisions for PARPi when given in combination with chemotherapy such that tumour cytotoxicity is maximized and bone marrow toxicity is minimized.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of early phase clinical trials have reported severe bone marrow toxicity with such therapeutic combinations [5][6][7][8][9][10] which could in part be attributed to suboptimal dosing schedules. 8 Non-invasive in vivo imaging of PARP-1 using a radiolabeled PARPi and techniques such as Positron Emission Tomography (PET) or Single-Photon Emission Tomography (SPECT) could be used to assess the duration of PARP-1 inhibition in different tissues. This could subsequently guide dosing decisions for PARPi when given in combination with chemotherapy such that tumour cytotoxicity is maximized and bone marrow toxicity is minimized.…”
Section: Introductionmentioning
confidence: 99%
“…HSP90 possesses an intrinsic ATPase activity that is required for mediating the necessary conformational changes in client proteins for activation (15,17,18) and is also important for stabilization of the HSP90 client proteins (19,20). HSP90 inhibitors 17-allylamino-17-demethoxygeldanamycin (17-AAG) as well as other structurally distinct agents, including SNX-5422 (also known as PF-04929113) and NVP-AUY922, bind to the nucleotide binding pocket of HSP90 and inhibit the progression of the HSP90 complex toward the stabilizing form resulting in the degradation of the client proteins (16,19,(21)(22)(23). It is well established that pharmacological inhibition of HSP90 can lead to degradation of a large variety of client proteins including kinases such as RAF kinase, ERBB2, AKT, v-SRC, and death domain kinase, the transcription factors mutants p53 and HIF-1␣, the mineralocorticoid, glucocorticoid, and mutant androgen receptors, and others such as the cystic fibrosis transmembrane conductance regulator CFTR and huntingtin (19, 21, 24 -32).…”
mentioning
confidence: 99%
“…Ideally, PARP inhibitor resistance is prevented by using drug combinations that completely eradicate tumors (1). To this end, established chemotherapeutic agents may be used, although these may also induce more severe side effects in the presence of PARP inhibitors (62,63). Alternatively, combination with other targeted therapeutics such as inhibitors for PI3 kinase (30,64), cell-cycle checkpoints (65) or other nicotinamide adenine dinucleotide metabolizing enzymes (66) may sensitize tumors to PARP inhibition.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%